MIMO from theory to implementation - Sibille, Alain; Oestges, Claude; Zanella, Alberto (Academic Press/Elsevier, 2011)
"Multiple Input-Multiple Output (MIMO) techniques were developed about a decade ago and have steadily invaded all aspects of wireless communications. The techniques promise to deliver vast improvements in radio network capacity, throughput and robustness - hugely important issues for wireless operators and manufacturers who are looking at an estimated 600 million mobile broadband users by 2011 (Cartagena). You'll find a 'one-stop-shop' resource for anyone needing to know what MIMO is and how it will be incorporated into future wireless system design. Professionals needing to bring their knowledge up to speed will find a comprehensive and up-to-date description of the underlying theory along with practical guidance on how the fundamental algorithms can be made to work in tomorrow's communication systems"--Provided by publisher.